AB0132 Antiphospholipid syndrome patients show an altered profile of endothelial progenitor cells and endothelial microparticles. (15th June 2017) - Barbati, C; Spinelli, FR; Miranda, F; Ceccarelli, F; Vomero, M; Massaro, L; Colasanti, T; Valesini, G; Alessandri, C; Conti, F
Abstract : Background: Antiphospholipid Syndrome (APS) is an autoimmune disease characterized by recurrent thromboembolic events and pregnancy morbidity associated to the presence of specific serum antibodies directed against membrane phospholipids and proteic co-factors (1). Endothelial dysfunction represents the earlier and reversible stage of subclinical atherosclerosis that characterizes these patients. An altered profile of endothelial progenitor cells (EPCs) and endothelial microparticles (EMPs) could promote endothelial damage (2). Few studies suggested that EMP release is stimulated by circulating anti-phospholipids (aPL). A previous study on EPC reservoir in 7 APS patients showed no difference compared to healthy subjects. Objectives: Our aim was to evaluate circulating EPCs and EMPs in primary APS patients (PAPS). Methods: We studied primary APS patients with previous thromboembolic events and sex and age-matched healthy controls (HC). Circulating EPCs was identified by flow cytometry analysis as CD34+/KDR+ positive cells isolated from peripheral blood mononuclear cells (PBMCs); EMPs was obtained by centrifugation of whole blood and quantified by flow cytometry (CD31+/CD41a-). Data were expressed a s mean±standard deviation or median (interquartile range) when appropriate; correlations between EPC and EMP levels with aPL were investigated by Spearman test. P values <0.05 were considered statistically significant. Results: We enrolled 12 PAPS patients (mean age 44±12 years) and 12 HC. Compared to HC, PAPS patients showed a lower EPC percentage (0.01±0.006% vs 0.04±0.003%, p=0.0008) and a higher EMP number (104±80 MPs/microliter vs 20±8, p<0.0001). EMPs number positively correlated with anticardiolipin and antibeta2 glicoprotein I, both IgM and IgG (p<0.05 and r>0.7 for all correlations). Conclusions: The results of this study suggest that endothelial cells, activated by circulating aPL, release EMPs that can perpetuate the endothelial damage. Moreover, our cohort of APS patients has a reduced number of circulating EPC that could contribute to the impairment of endothelial repair. Both the chronic endothelial damage and the lack of an efficient repair could contribute to the progression of atherosclerosis in PAPS patients. References: Miyakis S, Lockshin MD, Atsumi T, Branch DW, Brey RL, Cervera R, Derksen RH, DE Groot PG, Koike T, Meroni PL, Reber G, Shoenfeld Y, Tincani A, Vlachoyiannopoulos PG, Krilis SA. International consensus statement on an update of the classification criteria for definiteantiphospholipid syndrome (APS). J. Thromb. Haemost. 2006 Feb;4:295–306. Bartoloni E, Alunno A, Bistoni O, Caterbi S, Luccioli F, Santoboni G, Mirabelli G, Cannarile F, Gerli R. Characterization of circulating endothelial microparticles and endothelial progenitor cells in primary Sjögren's syndrome: new markers of chronic endothelial damage? Rheumatology (Oxford). 2015 Mar;54:536–44. Disclosure of Interest: None declared